Nicotinamide phosphoribosyltransferase secreted from microglia via exosome during ischemic injury - Lu, Yun‐Bi; Chen, Chen‐Xiang; Huang, Jing; Tian, Yu‐Xin; Xie, Xian; Yang, Ping; Wu, Ming; Tang, Chun; Zhang, Wei‐Ping (Journal of neurochemistry, 2019)
Nicotinamide phosphoribosyltransferase (NAMPT) is the key enzyme of the salvage pathway of nicotinamide adenine dinucleotide synthesis. NAMPT can also be secreted and functions as a cytokine. We have previously shown that in the brain, NAMPT expression and secretion can be induced in microglia upon neuroinflammation and injury. Yet the mechanism for NAMPT secretion remains unclear. Here we show that NAMPT can be actively secreted from microglia upon the treatment of ischemia‐like injury – oxygen‐glucose deprivation and recovery (OGD/R). We confirmed that classical ER‐Golgi pathway is not involved in NAMPT secretion. NAMPT secretion was further enhanced by ATP, and the secretion was mediated by P2X7 receptor and by intracellular Ca2+. Importantly, we found that phospholipase D inhibitor, n‐butanol, phospholipase D siRNA, and wortmannin significantly decreased OGD/R‐induced and ATP‐enhanced release of NAMPT in microglia. After excluding the mechanisms of involving secretory autophagy, endosomes, and secretory lysosome, we have concluded that microglial NAMPT is secreted mainly via exosome. Immune‐electron microscopy identifies NAMPT in extracellular vesicles with the size and morphology characteristic of exosome. With the vesicles harvested by ultra‐centrifugation, exosomal NAMPT is further confirmed by Western blotting analysis. Intriguingly, the amount of NAMPT relative to exosomal protein markers remains unchanged upon the treatment of OGD/R, suggesting a constant load of exosomal NAMPT in microglia. Taken together, we have identified NAMPT is actively secreted via exosome from microglia during neuroinflammation of ischemic injury. We proposed a cascade for P2X7R‐mediated nicotinamide phosphoribosyltransferase (NAMPT) secretion from microglia through Ca2+‐dependent phospholipase D‐mediated exosomal pathway during cerebral ischemic injury: the activation of P2X7R evokes Ca2+ influx through the ion channel of P2X7R, the increment of intracellular [Ca2+] causes the activation of phospholipase D (PLD). The activated PLD (PLD*) catalyzes phosphatidylcholine (PC) to produce phosphatidic acid (PA). PA participates in the release of exosome that contains NAMPT. Our findings provide a new insight into the secretion pathways of NAMPT from microglia.